Direct Participation of Citizen in Democratic Decision Making at the Local Level - Fazliu, Ramiz (European Journal of Multidisciplinary Studies, 2016)
The Essence every proper democracy is characterized by the level of participation of citizens in decision-making for different local issues and affairs. The right of direct participation of citizens in decision-making on local issues proclaimed even by the norms prescribed by domestic legal frame (countries apart) but also internationally, which determine in an almost standardize form the participation of citizens in decision-making such as civic initiatives, gatherings of citizens, referendum, public audience, polls, surveys, petitions etc. Through these forms of participation citizens are directly involved in making decisions about local affairs and issues related to the life and the common interests of the local level. Therefore, people with their participation can influence in decision-making in various fields, such as, in the area of decision-making for local policies dealing with legal acts (regulations and other local acts), plans and programs, as well as concrete development projects at the local level. The object of this paper deals with the most common forms of citizen’s participation in decision making at the local level which are illustrated with some concrete examples on how is regulated by legal norms and practically implemented in some countries with developed democracies: the USA, Great Britain, Switzerland and the countries of Central and Southeastern Europe such as Estonia, Hungary, Kosovo